Evolving Paradigms in the Treatment of Atrial Septal Defects With Pulmonary Arterial Hypertension. Issue 6 (November 2021) - Sathananthan, Gnalini; Levy, Robert D.; Swiston, John; Brunner, Nathan W.; Bradley, Elisa A.; Kiess, Marla; Grewal, Jasmine
Abstract : Atrial septal defects are one of the most frequently diagnosed congenital heart defects in adulthood. The presence of concurrent moderate or severe pulmonary arterial hypertension without Eisenmenger syndrome at the time of diagnosis can make for a challenging clinical scenario. There is continually evolving literature to determine the ideal approach to this subset of patients. Here we aim to review the clinical presentation, history, medical therapy, and closure options for atrial septal defects–pulmonary arterial hypertension with predominant left-to-right shunting, in the absence of Eisenmenger syndrome.